2004
DOI: 10.1002/erv.566
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a four‐month day treatment programme on alexithymia in eating disorders

Abstract: High prevalence rates of alexithymia have been reported in eatingdisordered patients. The aim of this study was first to investigate whether a 4-month day hospital treatment leads to a decrease in alexithymia in eating-disordered patients and second to see whether alexithymia predicts short-term outcome in this population. The Toronto Alexithymia Scale (TAS) and the Eating Disorder Inventory (EDI) were given to 47 patients with anorexia nervosa (n ¼ 18), bulimia nervosa (n ¼ 25) and eating disorders not otherw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 15 publications
3
52
0
3
Order By: Relevance
“…But only AAET increased assertiveness and emotional processing, whereas RT did not. Also, only AAET reduced alexithymia, a construct that has both trait and state components and that has been found to decrease in response to emotion-oriented interventions (61, 62). Emotional expression, however, did not change significantly in response to AAET, although it showed the expected trend in analyses of those participants who attended all sessions.…”
Section: Discussionmentioning
confidence: 95%
“…But only AAET increased assertiveness and emotional processing, whereas RT did not. Also, only AAET reduced alexithymia, a construct that has both trait and state components and that has been found to decrease in response to emotion-oriented interventions (61, 62). Emotional expression, however, did not change significantly in response to AAET, although it showed the expected trend in analyses of those participants who attended all sessions.…”
Section: Discussionmentioning
confidence: 95%
“…Difficulties distinguishing between NEs have also been associated with elevated binging, purging, and fat-checking behaviors in nonclinical samples (Carano et al, 2006;De Berardis et al, 2007;Fink, Anestis, Selby, & Joiner, 2010). However, in other studies, researchers have not found a significant association between low NED and weight-loss behaviors (Becker-Stoll & Gerlinghoff, 2004;De Berardis et al 2007;Rastam, Gillberg, Gillberg, & Johansson, 1997). One potential explanation for these inconsistent findings is that these researchers have all examined NED, whereas no researchers to date have examined low PED, particularly in individuals with anorexia.…”
Section: Anorexia Emotional Distortion and Emotion Differentiationmentioning
confidence: 98%
“…These questions are of obvious value not only from a clinical perspective but also from a theoretical viewpoint because one can demonstrate that a risk factor such as alexithymia actually contributes to health problems only by reducing or removing it and seeing whether health improves. Some studies have shown that alexithymia decreases over time during treatment of eating disorders (Becker-Stoll & Gerlinghoff, 2004;Clyne & Blampied, 2004;de Groot, Rodin, & Olmsted, 1995), yet these interventions were not attempting to reduce alexithymia directly, and the decrease in alexithymia may have been a reflection of reduced symptoms. Furthermore, these studies did not have control or comparison conditions to assess changes in alexithymia in the absence of treatment or given a different treatment.…”
Section: Can Alexithymia Be Reduced?mentioning
confidence: 99%